CD38 in Adenosinergic Pathways and Metabolic Re-programming in Human Multiple Myeloma Cells: In-tandem Insights From Basic Science to Therapy - Horenstein, Alberto L.; Bracci, Cristiano; Morandi, Fabio; Malavasi, Fabio (Frontiers in Immunology, 2019)
Tumor microenvironments are rich in extracellular nucleotides which are metabolized by ectoenzymes to produce adenosine, a nucleoside involved in the control of immune responses. Multiple myeloma, a plasma cell malignancy developed within a bone marrow niche, exploits adenosinergic pathways to customize the immune homeostasis of the tumor. All stages of the myeloma disease overexpress CD38, a protein playing a dual role of receptor and ectoenzyme. At neutral and acidic pH, CD38 catalyzes the extracellular conversion of NAD+ to regulators of calcium signaling. Initial disassembly of NAD+ is also followed by an adenosinergic activity, provided that CD38 is operating in the presence of CD203a and CD73 nucleotidases and a proper environmental pH. cAMP extruded from tumor cells also serves as a substrate for metabolizing nucleotidases to signaling adenosine. These salvage pathways flank or bypass the canonical pathway based on the conversion of ATP by CD39. Both networks may be hijacked by the tumor controlling the homeostatic reprogramming of the myeloma in the bone marrow. In this context, adenosine assumes the role of a local hormone: cell metabolism is adjusted via low- or high-affinity purinergic receptors expressed by immune and bone cells as well as by tumor cells. These actions lead to immunosuppression, thus contributing to the failure of immune surveillance in cancer. Similar metabolic strategy is adopted to silence immune effectors during the progression of indolent gammopathies to symptomatic overt disease. Elevated levels of adenosine detected in plasma from myeloma aspirates were due to interactions taking place between myeloma and other cells lining the niche. There is a parallel between adenosine levels and disease progression, with patients with symptomatic myeloma usually having high adenosine. This is statistically reflected in the International Staging System for multiple myeloma. Beside the conventional use to deplete CD38+ malignant cell population, anti-CD38 antibodies are involved in the polarization and release of microvesicles, known to express several molecules able to produce adenosine. These adenosinergic pathways have become new immune checkpoints which improved immunotherapy protocols aimed at re-engaging the depressed immune system.